2013
DOI: 10.1002/pri.1565
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic Exercise is as Effective as dry Land Training to Blood Pressure Reduction in Postmenopausal Hypertensive Women

Abstract: This is a randomized controlled study that demonstrates the antihypertensive efficacy of aerobic aquatic exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
1
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(78 citation statements)
references
References 19 publications
2
63
1
6
Order By: Relevance
“…For the water-exercise group, these findings agree with those of 2 previous studies of obese women and type 2 diabetes patients [23,36] but disagrees with another of obese women [24]. Finally for the dryland-exercise group, our results agree with our previous report [9][10][11], but one study found higher BP reduction [8].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…For the water-exercise group, these findings agree with those of 2 previous studies of obese women and type 2 diabetes patients [23,36] but disagrees with another of obese women [24]. Finally for the dryland-exercise group, our results agree with our previous report [9][10][11], but one study found higher BP reduction [8].…”
Section: Discussionsupporting
confidence: 83%
“…For the water-exercise group, our results agree with a previous study showing reduced glycated hemoglobin and triglyceride levels in patients with type 2 diabetes [36] but disagree with 2 other studies of overweight women [22,23]. Regarding lipid variables, we found no improvements in the water and dryland-exercise groups, which agrees with previous studies of overweight women (water training) [22,23] and obese subjects after Med and dryland HIIT [8][9][10].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In addition, we included studies on aerobic PA by hypertensive individuals, where the dose of activity was not possible to delineate, for example, a number of studies on walking where such detailed description of aerobic dose was not possible 39–43. Also, a number of other RCT studies including unspecified aerobic activity, such as water training,44 45 dance46 and soccer,47 were included in the analysis. In summary, the mean BP lowering effect of aerobic training in hypertensive patients, in the included RCT studies, was 10.8/4.7 mm Hg, with 3+ level of evidence.…”
Section: Introductionmentioning
confidence: 99%
“…PWV reductions are often accompanied with a reduction in central and peripheral blood pressure, therefore a reduction in central blood pressure may precede changes in AS. Multiple studies [5,50,51] have all shown that that aquatic based exercise is as effective as land based exercise at reducing blood pressure.…”
Section: Aquatic Exercise Interventionmentioning
confidence: 99%